2019
DOI: 10.1186/s40001-019-0389-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics associated with primary cardiac angiosarcoma outcomes: a surveillance, epidemiology and end result analysis

Abstract: Background Primary cardiac angiosarcoma (PCAS) is a rare type of tumour. Furthermore, descriptions of the demographic features and prognostic factors of PCAS patients have been poorly reported. Methods A population cohort study was conducted using retrospectively extracted data from the SEER (Surveillance, Epidemiology and End Results) database for patients with histological diagnoses of PCAS; the extracted information included demographic, treatment and outcome data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
(30 reference statements)
0
33
0
Order By: Relevance
“…Conic et al analyzed the outcome of cutaneous AS patients and disclosed no significant impacts of RT on OS [ 3 ], same results were confirmed by Buehler et al and Zhang et al [ 11 , 26 ]. In contrast, Ogawa et al [ 19 ] reported that RT effectively improved OS in 48 patients with localized AS of the scalp and face.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Conic et al analyzed the outcome of cutaneous AS patients and disclosed no significant impacts of RT on OS [ 3 ], same results were confirmed by Buehler et al and Zhang et al [ 11 , 26 ]. In contrast, Ogawa et al [ 19 ] reported that RT effectively improved OS in 48 patients with localized AS of the scalp and face.…”
Section: Discussionmentioning
confidence: 72%
“…The results of the earlier studies regarding the relation between tumor grade and patients’ survival time varied. A number of previous studies have documented no association of tumor grade with OS of AS [ 7 , 26 ]. Conversely, Kathryn et al [ 20 ] reported that higher tumor grade is predictive of greater risk of death in primary mediastinal sarcoma, conflicting with the conclusion reached by Brett et al and Manjari et al [ 21 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis on 168 primary cardiac angiosarcomas selected from the National Cancer Institute's SEER database confirmed data about outcomes associated with RT. The mean survival rate was higher in patients who underwent radiotherapy (63% higher than controls at univariate analysis) [73].…”
Section: Radiotherapymentioning
confidence: 84%
“…As for the histologic grade, a recent study concluded AS with grade III histology tended to experience a shorter survival which was consistent with our result 15 . The median survival time of AS was various in different primary sites [16][17][18] , but which site with the highest mortality has not been well documented. Our study elaborated AS from bone harbored the highest risk compared with soft tissue, heart mediastinum and peritoneum.…”
Section: Discussionmentioning
confidence: 99%